2001
DOI: 10.1046/j.1365-2540.2001.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

Late male-killing phenomenon found in a Japanese population of the oriental tea tortrix, Homona magnanima (Lepidoptera: Tortricidae)

Abstract: A female-biased sex ratio was found in the oriental tea tortrix, Homona magnanima (Lepidoptera: Tortricidae), in Tsukuba, Ibaraki, Japan. There was no difference in mean egg hatch between the all-female and normal strains. Greater than 50% mortality was observed in the all-female strain larvae, suggesting that female-only broods are produced as a result of late male-killing. The female-biased sex ratio was maternally inherited and maintained, even when females were backcrossed with males of the normal strain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…(a) Purification of the male-killing agent Late male killing in H. magnanima is transmitted vertically only from mothers (Morimoto et al 2001). The causal agent of late male killing in H. magnanima is not Wolbachia, Spiroplasma, Rickettsia, Flavobacteria or the gamma proteobacteria, which were reported to be early male-killing agents, or the protozoa reported to be the late male-killing agent in mosquitoes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(a) Purification of the male-killing agent Late male killing in H. magnanima is transmitted vertically only from mothers (Morimoto et al 2001). The causal agent of late male killing in H. magnanima is not Wolbachia, Spiroplasma, Rickettsia, Flavobacteria or the gamma proteobacteria, which were reported to be early male-killing agents, or the protozoa reported to be the late male-killing agent in mosquitoes.…”
Section: Resultsmentioning
confidence: 99%
“…The normal strain of H. magnanima was collected from Itsukaichi, Tokyo, Japan, in 1999. These strains were maintained as described previously (Morimoto et al 2001).…”
Section: (A) Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five clades of bacteria have been identified as early male-killing agents (Rickettsia, Wolbachia, Spiroplasma, Flavobacteria, and a gamma proteobacterium) (Hurst et al, 2003;Majerus, 2003). Late male killing was previously recorded only in mosquitoes and is caused by a microsporidium (Andreadis and Hall, 1979;Andreadis, 1985) but our group recently found late male killing in the oriental tea tortrix Homona magnanima (Diakonoff) collected from Ibaraki Prefecture, Japan (Morimoto et al, 2001). Morimoto et al (2001) reported that the causative agent of late male killing of H. magnanima is maternally heritable, horizontally transmissible, and microorganisms that cause other male-killing phenomena, such as Wolbachia, Spiloplasma, Rickettsia, or microsporidia, are not responsible.…”
Section: Introductionmentioning
confidence: 92%
“…LMK females were crossed with NSR males and maintained in the laboratory (Morimoto et al, 2001). In each generation, 20 female and 30 male pupae were placed in a plastic box (30ϫ20ϫ5 cm) with wax paper for oviposition.…”
Section: Insectsmentioning
confidence: 99%